2000
DOI: 10.1177/002246690003400305
|View full text |Cite
|
Sign up to set email alerts
|

Technical Adequacy of the Maze Task for Curriculum-Based Measurement of Reading Growth

Abstract: The purpose of the present study was to examine the technical adequacy of curriculum-based measurement (CBM) for assessing student growth over time. Participants were 43 second graders whose reading performance was measured monthly over 1 school year with the maze task. Technical characteristics of the CBM maze task were examined in terms of reliability, sensitivity, and validity for assessing student growth. Results showed that the maze task had good alternate-form reliability, with a mean coefficient of .81 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
89
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(97 citation statements)
references
References 22 publications
(42 reference statements)
7
89
0
1
Order By: Relevance
“…A student's score consists of the average number of words selected correctly minus the number of words selected incorrectly across the three passages. The test-retest reliability is .83 (Shin et al, 2000).…”
Section: Cbm-maze Testmentioning
confidence: 97%
See 1 more Smart Citation
“…A student's score consists of the average number of words selected correctly minus the number of words selected incorrectly across the three passages. The test-retest reliability is .83 (Shin et al, 2000).…”
Section: Cbm-maze Testmentioning
confidence: 97%
“…CBM measures have been shown to be highly sensitive to growth over brief periods (see Espin, McMaster, Rose, & Wayman, 2012, for a review). Specifically, for the assessment of reading comprehension, the CBM-Maze test is established as a reliable and valid measure to assess progress (Espin, Wallace, Lembke, Campbell, & Long, 2010;Fuchs & Fuchs, 2002;Marcotte & Hintze, 2009;Pierce, McMaster, & Deno, 2010;Shin, Deno, & Espin, 2000;Tichá, Espin, & Wayman, 2009). The test has a standardized cloze format (Fuchs & Fuchs, 1992): Every seventh word is deleted and replaced with three multiple-choice alternatives-one correct and two incorrect words.…”
mentioning
confidence: 99%
“…As a student reads the passage, he/she is instructed to circle the word that makes the most sense in the sentence. Several studies support the use of Maze as a valid and reliable measure of students' reading skills for elementary and secondary students (Brown-Chidsey, Davis, & Maya, 2003;Espin & Foegen, 1996;Fuchs & Fuchs, 1992; Miura-Wayman, Wallace, Ives-Wiley, Tichá, & Espin, 2007;Shinn, Deno, & Espin, 2000;Tichá, Espin, & Wayman, 2009). Maze may also address concerns regarding the decline in sensitivity of WCPM as student grade level increases: Jenkins and Jewell (1993) found that Maze may actually be more sensitive to reading skills at higher grades than at lower grades.…”
Section: Wcpmmentioning
confidence: 98%
“…In recent research, a silent reading assessment task design-known as the maze technique-has gained empirical support as an indicator of basic reading efficiency and comprehension (Fuchs & Fuchs, 1992;Shin, Deno, & Espin, 2000). The design uses a forced-choice cloze paradigm-that is, in each sentence within a passage, one of the words has been replaced with three choices, only one of which makes sense in the sentence.…”
Section: Subtest 5: Efficiency Of Basic Reading Comprehensionmentioning
confidence: 99%